South East Europe Regular Economic Report No. 6 : Brittle recovery - World Bank (Washington, DC, 2014)
This report covers economic developments, prospects, and policies in six South Eastern European countries (SEE6): Albania, Bosnia and Herzegovina, Kosovo, FYR Macedonia, Montenegro, and Serbia. South East Europe (SEE6)'s economy recovered from the 2012 recession, growing by 2.2 percent on average in 2013. Each of the SEE6 countries marked positive growth rates in 2013, with growth at or exceeding 3 percent in Kosovo, FYR Macedonia and Montenegro. External demand for SEE6 exports, especially by the European Union (EU), was the key driver of the recovery. On the production side, SEE6 drivers of growth were mixed, but in all countries a good agricultural year supported economic activity. An export-led recovery combined with depressed domestic demand resulted in a significant narrowing of current account imbalances in all SEE6 countries. Foreign direct investment (FDI) and portfolio investment financed most of the current account deficits in SEE6. Overall, SEE6 countries are having limited success in translating the economic recovery into job creation. SEE6 countries reduced their fiscal deficits to 3.8 percent of GDP in 2013 from 4.3 percent of GDP in 2012. The pace of fiscal adjustment and still nascent economic growth were insufficient to reverse public debt dynamics in SEE6. In a low-inflation environment, SEE6 central banks moderately loosened monetary policy. The financial sector remained broadly stable, albeit fragile, in the course of 2013. The SEE region is projected to grow at 1.9 percent in 2014 and 2.6 percent in 2015 on the back of external demand. The positive growth since mid-2013 and the still accommodative monetary conditions of the Euro Area are likely to continue help SEE6 exports to grow, despite notable risks related to the outlook for the Euro Area (related to the slow reform implementation and prolonged period of low inflation or risk of deflation).